2018
DOI: 10.14393/bj-v34n3a2018-39372
|View full text |Cite
|
Sign up to set email alerts
|

Distillation methods affect the chemical composition of Varronia curassavica Jacq. essential oil?

Abstract: The objective of this work was to evaluate the chemical composition of essential oil from Varronia curassavica Jacq. obtained by microwave (MI) and hydrodistillation (HD) extraction methods. The MI method tested three powers (500, 600, and 700W), three distillation times (20, 30, and 40 min.), and three water volumes (0, 25, and 50 mL per sample). The HD method tested three distillation times (100, 120, and 140 min.) and three water volumes (1.0, 1.5, and 2.0 L per 3-liter flask). The essential oils were analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Leaf drying and the appropriate storage allow better plant material conservation. Thus, the drying process is widely used, but it must be performed in a way that does not compromise the product quality at the end of the production process (MARCHESE; FIGUEIRA, 2005). In a study with Myrcia lundiana, Alves et al (2018) reported that one-day drying at 40 ° C was enough to dry the leaves without affecting the essential oil content.…”
Section: Patchouli [Pogostemon Cablin (Blanco)mentioning
confidence: 99%
“…Leaf drying and the appropriate storage allow better plant material conservation. Thus, the drying process is widely used, but it must be performed in a way that does not compromise the product quality at the end of the production process (MARCHESE; FIGUEIRA, 2005). In a study with Myrcia lundiana, Alves et al (2018) reported that one-day drying at 40 ° C was enough to dry the leaves without affecting the essential oil content.…”
Section: Patchouli [Pogostemon Cablin (Blanco)mentioning
confidence: 99%
“…Essential oils are a complex mixture of volatile molecules with large variation in their composition. They can be used in the synthesis of various products (NIZIO et al, 2018).…”
Section: Lantana Camaramentioning
confidence: 99%